A review on the pharmacological properties, toxicological characteristics, pathogenic mechanism and analytical methods of aristolochic acids. (2nd October 2021) - Zhang, Miaomiao; Liu, Haiyan; Han, Yamei; Bai, Ligai; Yan, Hongyuan
Abstract: Aristolochic acids (AAs) are a kind of nitrophenanthrene carboxylic acids. Many scholars have conducted a lot of research on the pathological mechanism of AA. It is found that AA is not only related to renal failure, but also may lead to urinary tract urothelial cell carcinoma (UUC), gastric toxicity and reproductive organ toxicity. This article summarizes pharmacological properties, toxicological characteristics, pathogenic mechanism and analytical methods of AAs. Through reviewing this article, it is hoped that medical personnel and researchers will have an objective and comprehensive understanding of AAs to guide the clinical use of herbal medicine containing AAs.